Effect of the international copper price’s quote on corporate income tax collection in the mining sector - Lévano Huamaccto, Ronald Studer (2021)
Objective: Establish the effect of the international copper price’s quote on the corporate income tax collection (RIRE) of the Peruvian mining sector for the period 2004-2020. Method: The design was non-experimental, retrospective, cross-sectional and analytical, with a quantitative, descriptive, correlational, and explanatory approach. In this sense, inferential statistics were used, applying the Shapiro Wilk normality test, as well as hypothesis tests to determine the relationship between the study variables and regression analysis to establish the impact between them. Result: There is a positive relationship between the international copper price and the corporate income tax collection of the Peruvian mining sector, with a correlation degree of 86,9% and a determination coefficient of 75,52%, at a confidence level of 99%. Conclusion: The international copper price did affect the corporate income tax collection of the Peruvian mining sector in the period 2004-2020.